Erratum: Tuning a cellular lipid kinase activity adapts hepatitis C virus to replication in cell culture - Harak, Christian; Meyrath, Max; Romero-Brey, Inés; Schenk, Christian; Schult, Philipp; Esser-Nobis, Katharina; Schnitzler, Paul; Gotthardt, Daniel; Bartenschlager, Ralf; Lohmann, Volker (Nature microbiology, 2017)
Nature Microbiology 2, 16247 (2016); published online 19 December 2016; corrected 23 January 2017 In the original version of this Article, co-author Raffaele De Francesco's name was coded wrongly resulting in it being incorrect when exported to citation databases. This has now been corrected, thoughno visible changes will be apparent.
Gesehen am 23.10.2019